Prefrontal and midline interactions mediating behavioural control. - GARAVAN, HUGH PATRICK (Blackwell, 2009)
Top-down control processes are thought to interact with bottom-up stimulus-driven task demands to facilitate the smooth execution of behaviour. Frontal and midline brain areas in humans are believed to subserve these control processes but their distinct roles and the interactions between them remain to be fully elucidated. In this functional magnetic resonance imaging (fMRI) study, we utilized a GO/NO-GO task with cued and uncued inhibitory events to investigate the effect of cue-induced levels of top-down control on NO-GO trial response conflict. We found that, on a within-subjects, trial-for-trial basis, high levels of top-down control, as indexed by left dorsolateral prefrontal activation prior to the NO-GO, resulted in lower levels of activation on the NO-GO trial in the pre-supplementary motor area. These results suggest that prefrontal and midline regions work together to implement cognitive control and reveal that intra-subject variability is reflected in these lateral and midline interactions.
PUBLISHED
Keywords: anterior cingulate cortex ? cognitive control ? dorsolateral prefrontal cortex ? fMRI ? human ? pre-supplementary motor area